(3GdGhQGb GdfbOjI aj GdGbJUGO GdGSdGej (B:s (3bjeJgG hGMcGegG (B/s - (3GMeO, MSjfs ((3OeTb(B: s (3OGQ GdacQ(B, s, 1999)
(3XgQJ GdChQGb GdfbOjI Ydi GKQ GdMQH GdYGdejI GdGhdi SfI (B1914 (3ade JYO GdOhd efP Pdc GdJGQjN JSeM HGdJYGed HGdPgH hGdaVI cGdSGHb , hGRGA Pdc GNJdaJ hLgGJ GdfXQ dOi GdYdeGA aj eOi JWHjb GdCMcGe GdabgjI GdeJYdbI HGdOfGfjQ GdPgHjI hGdOQGge GdaVjI Ydi GdChQGb GdfbOjI hdbO JhUdJ GdCHMGK aj gPG GdcJGH Gdi Jcja Gdabgj ddChQGb GdfbOjI HEdMGbgG HGdPgH hGdaVI HGdGSJfGO Cdi GdJGgjd Gdabgj hGdcTa Yf GdCOdI aJJHY GdHGMK JGQjN GdfbhO Ke LeY CQGA GdabgGA aj eSGFdgG haUd GdCOdI GdCUhdjI aj GYJeGO GdChQGbGdfbOjI aGdcJGH jHMK aj JZjQ bjeI GdfbhO heG jJQJH Ydjg ef GfNaGV GdbhI GdTQGFjI GdCeQ GdPj jDOj Gdi NSGQI GdOGFf LRA ef Ojfg (B...... (3ceG jHMK aj HYV GdeYGedGJ GdeUQajI GdeYGUQI (B.s
Keywords: (3GbJUGO GSdGejs; (3GdfbhOs; (3GhQGb fbOjIs